Impact of reduced P‐glycoprotein function on digoxin concentrations in patients with dementia. Issue 10 (19th August 2019) - Ali, Izna; Guidone, Daniel; Nicolazzo, Joseph A.; Brouwer, Kim L.R.
Abstract : Aims: Patients with Alzheimer's disease (AD), the most common form of dementia, have reduced P‐glycoprotein (P‐gp) function at the blood–brain barrier. However, the effect of AD on P‐gp function in peripheral organs, and the impact on medication efficacy and toxicity is unknown. In this study, clinical chart review and physiologically based pharmacokinetic (PBPK) modelling were employed to determine whether disease‐associated changes in P‐gp could be assessed from clinically measured digoxin concentrations in patients without and with dementia. Methods: A retrospective chart review was conducted to compare digoxin dose and concentrations between cohorts. A PBPK model was developed to simulate changes in digoxin concentrations at single and multiple 62.5 and 125 μg/d doses due to reduced P‐gp function in peripheral organs. Results: Digoxin concentrations were similar between the nondementia ( n = 75) and dementia ( n = 72) cohorts (mean ± standard deviation; 0.64 ± 0.31 and 0.60 ± 0.34 ng/mL, respectively; −0.06 to 0.15, 95% confidence interval of difference). PBPK simulations showed that reduced P‐gp function resulted in a significant increase in digoxin exposure (AUC), but not in Cmax . For example, when a 2‐fold reduction in P‐gp function was simulated in older people following multiple 125 μg/d digoxin doses, the AUC over the last dosing interval was increased compared to baseline (24.29 ± 3.94 vs 17.04 ± 3.46 ng/mL*h; 4.52 to 9.98); however, Cmax was similar (1.38 ± 0.20 vs 0.99 ± 0.18 ng/mL; −2.33 to 3.13). Conclusion: Clinically measured digoxin concentrations were not statistically different in patients with dementia. Based on PBPK simulations, digoxin AUC may need to be evaluated to adequately assess the impact of reduced P‐gp function in peripheral organs.